TESS Investigation—Demographics of Young Exoplanets (TI-DYE). III. An Inner Super-Earth in TOI 2076 - Madyson G. Barber; Andrew W. Mann; Andrew Vanderburg; Andrew W. Boyle; Ana Isabel Lopez Murillo (The Astronomical Journal)
Young (<500 Myr) multiplanet transiting systems are valuable environments for understanding planet evolution by offering an opportunity to make direct comparisons between planets from the same formation conditions. TOI 2076 is known to harbor three 2.5–4 R _⊕ planets on 10–35 days orbits. All three are JWST cycle 3 targets (for transmission spectroscopy). Here, we present the detection of TOI 2076 e; a smaller (1.35 R _⊕ ) inner (3.02 days) planet in the system. We update the age of the system by analyzing the rotation periods, lithium equivalent widths, color–magnitude diagram, and variability of likely comoving stars, finding that TOI 2076 and comoving planetary system TOI 1807 are 210 ± 20 Myr. The discovery of TOI 2076 e is motivation to revisit known transiting systems in search of additional planets that are now detectable with new TESS data and updated search methods.